Reator anaeróbio- aeróbio com recirculação da fase líquida aplicado ao tratamento de efluente de abatedouro de aves - Lopes, Carla Limberger (2016)
The aim of this study was to evaluate a combined anaerobic-aerobic upflow fixed-bed reactor with recirculation of the liquid phase for the removal of nitrogen and organic matter from poultry slaughterhouse wastewater. The reactor was made of an acrylic tube of internal diameter of 93 mm and the length of 1000 mm with a useful volume of 5.6 L being 3.5 L corresponding to the anaerobic compartments and 2.1 L to the aerobic one. The bed for immobilization of the biomass was formed by expanded clay and polyurethane foam. For discussing the results, this study was divided into three articles. In the first article, was evaluated the reactor performance with respect to the elimination of nitrogen (≈65 mg.NT.L-1) and organic matter (≈600 mg.DQO.L-1) due to the recirculation rate (R = 0.5, 1 and 2) and the hydraulic retention time (HRT) of 11 h (6.8 h in anaerobic condition and 4.2 h in aerobic condition) over the time. The best operating condition was obtained at the recirculating rate of 2. In this condition, the total nitrogen removal was 65% with the effluent concentration of 6 mg.NH4+.L-1 e 12 mg.NO3-.L-1. For all condition, the organic matter removal was greater than to 95% with the effluent concentration of approximately 20 mg.COD.L-1. Thus, the increasing of the recirculation rate influenced positively in the reactor performance. In the second article, the hydraulic detention time was evaluated (HDT) at 14 h, 11 h and 8 h with the recirculation rate (R) of 0.5 (Step I), R = 1 (Step II) and R 2 = (Step III). The affluent average concentrations were 65 mg.NT.L-1, 580 mg.COD.L-1, 77 mg L-1 of total alkalinity and pH of 6.4. The samples were collected inlet and output of each compartment along the reactor height. In the Step I, the nitrification efficiencies were 76%, 70% and 41% respectively for 14 h, 8 h and 11 h, showing the effect of HRT. In all steps, the alkalinity has been regarded as the limiting factor of the process and its deficit was 10 to 30%. It was attributed to this factor the low efficiency of total nitrogen removal of about 45%. Throughout the experiment the removal efficiency of organic matter in terms of chemical oxygen demand (COD) was over 90% and made to fit the first order kinetic model for degradation of the substrate. In the third article, was evaluated the hydrodynamic behavior of this system, through stimulus response tests using eosin Y dye as tracer. It has been evaluated the hydraulic retention time of 8 h with three recirculation rates, of .0.5, 1 and 2 times. Under these conditions, the removal of organic matter was greater than 90% and nitrogen conversion was favored by applying lower loads of (0.18 Kg.N.m-3.d-1). It was found that the hydrodynamic evaluation showed the continuous-stirred reactors behavior with 2 to 2.5 reactors in series (N-CSTR).